La Commune de Paris - Audin, Michèle (La Commune de Paris)
Blog de Michèle Audin
Keywords: _open access

Nuremberg Trials (Harvard Law School Library's Nuremberg Trials Project)
The Harvard Law School Library's Nuremberg Trials Project is an open-access initiative to create and present digitized images and full-text versions of the Library's Nuremberg Trials documents, descriptions of each document, and general information about the trials. The project provides access to the documentary record and other associated materials for all thirteen trials. We currently offer page images and searchable document descriptions for all documents as well as searchable full-text versions for most prosecution exhibits and most of the trial transcripts. Both prosecution and trial exhibits as well as all trial transcripts are currently only offered in the English-language versions used at the time of the Trials. Important: when citing from documents and transcripts, always verify the exact wording by consulting the accompanying page images of the document in question. The full-text versions of transcripts and documents are a product of human- and computer-aided transcription and may deviate in small ways from the originals.
Keywords: _open access

Looking at Nuclear Weapons by Type: Introducing the Nuclear Weapon Systems Project - Facini, Andrew (The Council on Strategic Risks, 2023)
Diving into CSR's launch of a clear, concise repository of deployed nuclear weapons across their history.
Keywords: _open access

Waterloo Medal Roll (The Royal Mint Museum)
The names of all those who were awarded the campaign medal for taking part in the Battle of Waterloo were recorded in the Waterloo Medal Roll. It takes the form of a large beautifully leather-bound volume, exquisitely hand-written, with the names of the soldiers entered under their regi…
Keywords: _open access

Les infirmières décédées entre 1914 et 1921
Anges Blancs 1914-1918 est un site de recherche concernant les infirmières décédées durant la première guerre mondiale et jusque dans les années 1920.
Keywords: _open access

CIA Reading Room Historical Collections
declassified documents from the Cold War
Keywords: _open access

The Valley of the Shadow: Two Communities in the American Civil War
Keywords: _open access

Houston Mutiny and Riot Records (South Texas College of Law Houston Digital Collections)
Keywords: _open access

National WWI Museum and Memorial (National WWI Museum and Memorial)
The National WWI Museum and Memorial's online collections database allows you to search digital records of our global collection that began in 1920.
Keywords: _open access

Documents relatifs aux relations extérieures du Canada /Documents on Canadian external relations - Ministère des affaires extérieures Canada
1908-1963
Keywords: _open access

Publications gouvernementales - Canadiana
Find publications on a broad range of topics relating to indigenous rights, labour, justice, arts and literature, and the military.
Keywords: _open access

Independent Voices
About this Collection: Independent Voices is an open access digital collection of alternative press newspapers, magazines and journals, drawn from the special collections of participating libraries. These periodicals were produced by feminists, dissident GIs, campus radicals, Native Americans, anti-war activists, Black Power advocates, Hispanics, LGBT activists, the extreme right-wing press and alternative literary magazines during the latter half of the 20th century. Independent Voices is ma...
Keywords: _open access

Affiches de guerre - Calypso
La collection d’affiches de guerre des bibliothèques de l’Université de Montréal se compose de plus de 3000 images produites au cours des deux guerres mondiales ainsi que de l’entre-deux-guerres. Chaque affiche a été numérisée et son contenu a fait l’objet d’une description détaillée.
Keywords: _open access

Canadian Cultural History About The Spanish Civil War
Keywords: _open access

Democracy at War: Canadian Newspapers and the Second World War | La Démocratie en guerre : Les journaux canadiens et la Seconde Guerre mondiale
Musée canadien de la guerre : La démocratie en guerre : les journaux canadiens et la Seconde Guerre mondiale : contient plus de 140 000 coupures de presse, organisées par sujet et par date, regroupe des articles et des éditoriaux de journaux, pour la plupart canadiens, qui couvrent tous les aspects de la guerre.
Keywords: _open access

National Archives - The U.S. National Archives and Records Administration
Keywords: _open access